Perlindungan Hukum terhadap Perkawinan Warga Negara Kelompok Penghayat Kepercayaan dengan Agama Tertentu di Indonesia - Djessyka Dameria; Kadek Wiwik Indrayanti; I Gusti Ngurah Adnyana; Fadilla Dwi Lailawaty (University of Merdeka Malang, 2021)
The validity of marriage is the most important thing in the occurrence of marriage, where the validity of marriage is regulated in Article 2 of the Law of the Republic of Indonesia Number 19 of 2019 concerning amendments to Law Number 1 of 1974 concerning marriage, there is no explicit regulation (legal vacuum) regarding marriage. that occurs between citizens of certain beliefs and religions in Indonesia so that the validity of the marriage cannot be registered, therefore legal protection is needed for couples who carry out marriages between adherents of beliefs and certain religions in Indonesia to obtain the same rights as citizens